THE ROLE OF LITERARY LUMINARIES IN THE DEVELOPMENT OF URDU LANGUAGE AND NATIONAL THOUGHT (Contemporary Journal of Social Science Review, 2025)
This article explores the significant role of literary luminaries in the intellectual and linguistic development of the Urdu language, as well as their contribution to shaping national identity and cultural consciousness in Pakistan. From Quaid-e-Azam Muhammad Ali Jinnah’s ideological association with Urdu to Allama Iqbal’s intellectual advocacy and the literary achievements of iconic poets and writers, the paper underscores how Urdu evolved as a unifying national language in a multilingual society. It further examines the contributions of statesmen, linguists, and institutions that promoted Urdu through policy, education, and cultural expression. By analyzing key historical events, ideological discourses, and literary milestones, this study asserts that Urdu is not merely a medium of communication but a powerful cultural symbol that continues to guide national thought and integration.